A 25-year bibliometric study of implantable energy harvesters and self-powered implantable medical electronics researches. (June 2020) - Jiang, Dongjie; Shi, Bojing; Ouyang, Han; Fan, Yubo; Wang, Zhong Lin; Chen, Zhan-Ming; Li, Zhou
Abstract: Organisms and surrounding environment are filled with energy that can be converted into electricity by implantable energy harvesters (IEHs). More and more implantable medical electronics (IMEs) are evolving into self-powered devices with the support of the IEHs to break the limitation of service life of batteries used in them. Numerous researches aim to achieve the final goal of self-powered implantable medical electronics (SIMEs). After around one quarter century of research, it is an appropriate time to review the trend and prospect the future of related studies about IEHs and SIMEs. Based on the publications extracted from Web of Science (WOS) over the past 25 years (1995–2019), IEHs and SIMEs are analyzed and summarized based on bibliometric and visualization methods. Evolution trends and research characteristics of five types of IEHs and several highly representative SIMEs are discussed in depth. The findings show that implantable nanogenerator is the most concerned research topic and its research scale is expected to develop rapidly in the future. In addition, the publications of the promising SIMEs for clinical applications have also been highlighted and reviewed. Graphical abstract: In this study, bibliometric analysis methodology was used to visually present the development trends and research focus of the five types IEHs and some representative SIMEs based on IEHs. Meanwhile, the challenges and research emphases of IEHs and SIMEs in the future were suggested and predicted adequately. This report is meaningful for broad researchers to locate the research direction and content of SIMEs and IEHs. Image 1 Highlights: Spanning almost a quarter-century, this paper demonstrates the development trends and research focus of IEHs and SIMEs. Through the bibliometric analysis, the representative SIMEs and IEHs are emphasized. The great effort to forecast the challenges and research emphases of IEHs and SIMEs in the future.